Predictor Variables for Elevated Mood and Activity in Hypomania and Self-Actualization - Zaiets, Andrii (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The issue of overdiagnosis of hypomanic episodes is relevant due to their borderline nature. Diagnostic criteria describing elevated mood and activity, high self-esteem and productivity, is partly resembling a healthy process of self-actualization, which on the one hand leads to the already mentioned overdiagnosis, and on the other – to the social stigma of patients with bipolar disorder and medical and social prejudice against the elevated mood and activity they display. As part of this work, using correlation and regression, differentiation of high mood and high activity predictors is made in groups of people with a high level of self-actualization (n = 25) and patients diagnosed with the bipolar affective disorder without comorbidity (n = 24). A sample of healthy individuals with a normal level of self-actualization (n = 110) was also involved to control side variables and compare means. The following assessment inventories are used to collect data: Personal Orientation Inventory (Shostrom, 1963 – in the adaptation of SAT (Aleshina, Gozman, Zaika & Kroz, 1984)), shortened version of MMPI Mini-Mult (Zaitsev, Kozyula, 1981), FPI-B (Hampel & Selg, 1963 – adapted by Krylov, Ronginsky, 1989). The regression of the "hypomania" scale, Mini-Mult, as a dependent variable, showed different groups of predictors for the two studied samples. The statistics are summarized as a model of the relationship between elevated mood and activity predictors for the two groups. Significant differences in the configuration and elements of the linkages indicate the possibility of further development of this problem to create assessment tools and methodological guidelines for psychosocial care for groups at risk of developing or recurrence of bipolar disorder. Mainly, the difference in predicting variables consists of highly negative relation of cognitive needs to hypomania in the BAD group with highly positive direct affection of "schizoid" variable of Mini-Mult, whereas hypomanic trait in the self-actualizing group is affected by "schizoid" variable indirectly and is mainly subject of effect for "existential flexibility" and "time competence" variables.